Pengaruh Metode Pembelajaran Dan Motivasi Terhadap Hasil Belajar - Arsi Yulianjani (CICES (Cyberpreneurship Innovative and Creative Exact and Social Science), 2017)
The purpose of this study is to determine the influence of Learning Method on English learning outcomes, to determine the effect of learning motivation on English learning outcomes, and to determine the influence of learning method and motivation together with the results of Englishlearning. The research method uses experimental method. A sample of 80 students was selected randomly with a simple random technique. The data collection uses test instruments. The analysis of data uses descriptive statistics, Pearson's double correlation coefficient, Correlation of coefficient of determination and regression analysis. The statistical test uses t test and F test. This research was conducted on April 2015 until June 2015. The results showed: (1) There is a significant influence of Learning Method (X1) and Motivation (X2) together to the learning result of English (Y) students at SMK Negeri Tangerang. It can be proved by the value of F0 = 4,219 and Sig. = 0,000 <0.05. (2) There is a significant influence of Learning Method on English learning result of students at SMK Negeri in Tangerang. This is proved by the acquisition of Fo = 28,581 and Sig. = 0,000 <0.05. (3) There is a significant influence of learning motivation on English learning result of students at SMK Negeri in Tangerang. This is evidenced by the acquisition of Fo = 44.095 and sig. = 0,000 <0.05